2019
DOI: 10.1021/acs.jcim.8b00959
|View full text |Cite
|
Sign up to set email alerts
|

Ranking Reversible Covalent Drugs: From Free Energy Perturbation to Fragment Docking

Abstract: Reversible covalent inhibitors have drawn increasing attention in drug design, as they are likely more potent than noncovalent inhibitors and less toxic than covalent inhibitors. Despite those advantages, the computational prediction of reversible covalent binding presents a formidable challenge because the binding process consists of multiple steps and quantum mechanics (QM) level calculation is needed to estimate the covalent binding free energy. It has been shown that the dissociation rates and the equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 61 publications
2
51
0
Order By: Relevance
“…Although we were unable to observe the effect of the S272L mutation on HCN1 experimentally, we can assess its influence on channel gating in silico using free energy perturbation (FEP) (Rodinger and Pomès, 2005; Zhang et al, 2019). The free energy difference between the activation of HCN1 and its S272L mutant ∆∆G=∆ G r → a ( mut )−∆ G r → a ( HCN 1) were calculated using FEP (Zwanzig, 1954) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Although we were unable to observe the effect of the S272L mutation on HCN1 experimentally, we can assess its influence on channel gating in silico using free energy perturbation (FEP) (Rodinger and Pomès, 2005; Zhang et al, 2019). The free energy difference between the activation of HCN1 and its S272L mutant ∆∆G=∆ G r → a ( mut )−∆ G r → a ( HCN 1) were calculated using FEP (Zwanzig, 1954) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…While in most of these works the noncovalent and covalent states were considered, the authors of ref ( 17 ) used only the covalent state in their calculations. As pointed out in ref ( 19 ), the choice of considering just the covalent state is reasonable only when the contribution of the covalent state to the total binding free energy is at least −5.5 kcal/mol greater than that of the noncovalent state. Unfortunately, knowing a priori the contributions from the covalent and noncovalent states is not possible.…”
mentioning
confidence: 99%
“…The situation gets even further complicated when one tries to calculate the absolute covalent binding free energies, because in this case the possibility of error cancelation (as we might expect in relative free energy calculations) is negligible. One might still be able to calculate the absolute binding free energies by considering one inhibitor as a reference and following the thermodynamic cycle used in ref ( 19 ) to avoid the expensive quantum mechanics (QM)-based calculations. On the contrary, a complete mechanistic understanding of the covalent inhibition process is not possible from such analysis.…”
mentioning
confidence: 99%
“…Computational modeling of covalent modification can provide insights into the binding affinity, selectivity, and kinetics of these drugs . In two recent papers, Luo and coworkers have shown that the relative efficacy of covalent inhibitors can be related to the relative stabilities of the covalently bound adduct . The relative binding affinities of the covalent‐modifier drugs can be estimated using free‐energy perturbation so, in these cases, simulating the mechanism of covalent bond formation was not necessary.…”
Section: Introductionmentioning
confidence: 99%